Matemáticas en el Perú: un caso de responsabilidad social - Arias, Norma (2005)
A renowned corporate group states that there is a very important relationship between the development and the educational level of a people, and so decides to improve the mathematics school program as a way to improve academic performance. It starts by developing school texts with a new methodology and then, sponsored by other companies, it donates them to public educational institutions around the country. Shortly after, the program, Math for Everyone, seeks to increase its coverage and leaps to a virtual format, with an interactive proposal geared towards fun and games in order to catch the child and teenager’s attention.